ETHICS BASED BUSINESS FEASIBILITY : A LITERATURE REVIEW OF SUPERINDO’S CSR PRACTICES - Silvy Dewi Anggraini (Universitas Tulungagung, 2025)
This study aims to examine business feasibility from an ethical perspective by analyzing the implementation of Corporate Social Responsibility (CSR) at Super Indo, a retail company in Indonesia. Employing a literature review method, the study uses Keraf’s ethical framework, which encompasses social ethics, economic ethics, legal compliance, and stakeholder rights. The findings reveal that Super Indo consistently carries out CSR initiatives that contribute to social welfare, deliver economic value, comply with legal standards, and actively involve stakeholders. These efforts not only enhance corporate reputation but also influence consumer purchasing behavior. The study concludes that ethically grounded CSR can serve as a strong indicator of business feasibility in today’s competitive environment. However, the study is limited by its reliance on secondary data without primary empirical evidence. Future research should adopt qualitative or quantitative methods to provide deeper insight. This study serves as a reference for companies aiming to develop ethical and sustainable CSR strategies.